2022
DOI: 10.3390/nu14030657
|View full text |Cite
|
Sign up to set email alerts
|

Energy Requirements and Nutritional Strategies for Male Soccer Players: A Review and Suggestions for Practice

Abstract: Soccer is a high intensity intermittent sport, featuring critical events completed at high/maximal intensity which is superimposed onto an aerobic base of lower intensity activities and rest. Due to these varying energic demands and the duration of competition the need for optimal nutritional strategies to offset and delay fatigue are paramount. Over the last 50 years, several investigations have been reported on aspects of soccer be they nutrition-focused or those concerning the demands of the sport. Emanatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 146 publications
(237 reference statements)
0
17
0
1
Order By: Relevance
“…Ideally, an integrated approach, rigorous and consistent, combining internal and external loads is followed, as this provides more significant information about the load experienced by athletes than interpretations based on isolated data ( Bourdon et al, 2017 ; Impellizzeri et al, 2019 ; Miguel et al, 2021 ). In addition, several studies reported physical match loads to be affected by playing positions, tactical formation, the player themselves or different contextual factors (e.g., match location, environmental conditions, match importance, preparation, fixture congestion, season phase, match outcome, nutrition strategies, game rules) ( Link & de Lorenzo, 2016 ; Palucci Vieira et al, 2019 ; Julian, Page, & Harper, 2020 ; Altmann et al, 2021 ; Chmura et al, 2021 ; Forcher et al, 2022a ; Forcher et al, 2022b ; Hulton, Malone, Clarke, & MacLaren, 2022 ; Sarmento et al, 2022 ). Therefore, future studies elucidating such factors as well as integrating other components of match performance (especially technical and tactical) are warranted, to gain a holistic understanding of match performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, an integrated approach, rigorous and consistent, combining internal and external loads is followed, as this provides more significant information about the load experienced by athletes than interpretations based on isolated data ( Bourdon et al, 2017 ; Impellizzeri et al, 2019 ; Miguel et al, 2021 ). In addition, several studies reported physical match loads to be affected by playing positions, tactical formation, the player themselves or different contextual factors (e.g., match location, environmental conditions, match importance, preparation, fixture congestion, season phase, match outcome, nutrition strategies, game rules) ( Link & de Lorenzo, 2016 ; Palucci Vieira et al, 2019 ; Julian, Page, & Harper, 2020 ; Altmann et al, 2021 ; Chmura et al, 2021 ; Forcher et al, 2022a ; Forcher et al, 2022b ; Hulton, Malone, Clarke, & MacLaren, 2022 ; Sarmento et al, 2022 ). Therefore, future studies elucidating such factors as well as integrating other components of match performance (especially technical and tactical) are warranted, to gain a holistic understanding of match performance.…”
Section: Discussionmentioning
confidence: 99%
“…Advancements in technology made it possible to more accurately measure internal and external loads and thus the physical demands of soccer training and matches can now be better quantified ( Halson, 2014 ; Bourdon et al, 2017 ; Palucci Vieira, Carling, Barbieri, Aquino, & Santiago, 2019 ; Miguel et al, 2021 ; Torres-Ronda et al, 2022 ). Numerous studies assessed match loads of elite male, female, and youth soccer players regarding physical performance capacities, playing positions, tactical formation, or different contextual factors (e.g., match location, environmental conditions, match importance, preparation, fixture congestion, season phase, match outcome, nutrition strategies, game rules) ( Link & de Lorenzo, 2016 ; Palucci Vieira et al, 2019 ; Julian, Page, & Harper, 2020 ; Altmann et al, 2021 ; Chmura et al, 2021 ; Forcher et al, 2022a ; Forcher et al, 2022b ; Draper et al, 2022 ; Harkness-Armstrong, Till, Datson, Myhill, & Emmonds, 2022 ; Hulton, Malone, Clarke, & MacLaren, 2022 ; Sarmento et al, 2022 ). While the findings, especially at elite level, are not consistent, it is evident that data from one population group may not be relevant to other population groups ( Palucci Vieira et al, 2019 ; Saeterbakken et al, 2019 ; Reynolds et al, 2021 ; Forcher et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrate stores in the body are limited compared to fat stores. However, they play the most significant role in a football player's performance due to the muscle glycogen stored in the muscles [10,11]. Starting a match with full glycogen storage should be the standard, as otherwise, their depletion is a limiting factor for performance through reduced efficiency [12].…”
Section: Recommendations For Carbohydrate Intake By Football Playersmentioning
confidence: 99%
“…It combines high-intensity critical events like sprints and anaerobic activities with lower-intensity aerobic exercises and rest. It features rapid direction changes and extended periods of exertion [4]. Soccer players typically cover 10-14 km per match [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%